Evaluating the impact of experience value promotes user voice toward social media: Value co-creation perspective - Zhu, Wanying; Huangfu, Zhounan; Xu, Di; Wang, Xiuping; Yang, Ziang (Frontiers in Psychology, 2022)
Experience value is positively associated with user voice toward social media, but existing research lacks an examination of its mechanisms of action. Based on value co-creation theory, this paper explores the relationship between experience value (i.e. social value, entertainment value, information value) and customer voice, and explains the specific influence mechanism through the mediating role of user loyalty. The results of the empirical tests show that social value, entertainment value and information value have significant effects on user loyalty; user loyalty has a significant effect on promotive voice but not on prohibitive voice; user loyalty mediates the relationship between body social value, entertainment value, information value and promotive voice. The findings of this research reveal the important role of experience value on customer voice, which is an important guide for social media to achieve sustainable development.